Warfarin pharmacogenetics in patients with heart valve replacement - KARAALP, ATİLA; SÜSLEYİCİ, BELGİN; SÜNBÜL, MURAT (ELSEVIER, 2020)
Background: Warfarin treatment is crucial to prevent thrombolytic complications after the heart valve replacement (HVR) operation. Our purpose was to investigate the prevalence of CYP2C9 *2 and *3 gene polymorphisms, which are essential in warfarin metabolism in patients with and without HVR surgery prescribed with warfarin. Material and method: 47 patients with and without HVR were genotyped for the CYP2C9*2 (rs1799853, 430 C> T), CYP2C9*3 (rs1057910, 1075 A> C) polymorphisms by PCR-RFLP assay. Results: Homozygous wild (CC), heterozygous and homozygous polymorphic (CT+TT) genotype frequencies of CYP2C9 *2 were determined respectively as 69.6% and 30.4% for patients with HVR; 79.2% and 20.8% for patients without HVR. Homozygous wild (AA) and heterozygous (AC) genotype frequencies of CYP2C9 *3 polymorphism were determined respectively as 73.9% and 26.1%f for patients with HVR; 79.2% and 20.8% for patients without HVR. CYP2C9 *2 and *3 genotype frequencies did not show any statistically significant difference between with and without HVR groups. Conclusion: In the present study, no significant difference was observed between patients with and without HVR with respect to CYP 2C9 *2 and *3 gene polymorphisms in Turkish subjects. Further studies with higher number of patients are needed to evaluate the importance of CYP 2C9 *2 and *3 pharmacogenetic testing in patients with HVR using warfarin.
Keywords: Warfarin; CYP2C9; Heart valve replacement; Polymorphism; REDUCTASE COMPLEX SUBUNIT-1; VITAMIN-K ANTAGONISTS; BLEEDING COMPLICATIONS; GENE POLYMORPHISMS; ANTICOAGULANT-THERAPY; CYP2C9 POLYMORPHISM; ATRIAL-FIBRILLATION; VKORC1; ASSOCIATION; VARIABILITY